Antioxidant Properties of Underutilized Bornean Dabai Fruit and its Potential Applications as a Nutraceutical Product - Jian Hung, Sam; Yen San, Chan; Jobrun, Nandong; Angela, Siner; Jibrail, Kansedo; Freddie, Panau (Trans Tech Publications Ltd, Switzerland, 2022)
It is no doubt that plants are a vital centerpiece and contributed immensely in the health care industry. Besides, it has been found that the indigenous people in developing countries had long been using local traditional plants for the treatment of diseases. The traditional plants are highly valued for their bioactive compounds which exhibits high antioxidant activity and has the potential in bringing down the risk of diseases. Canarium odontophyllum, also called dabai is one of the underutilized traditional plants consumed by the indigenous people in Borneo Island. The objective of this research is to characterize the antioxidant activity, metal chelating activity, the hydroxyl radical scavenging activity and identifying the potential bioactive compounds of dabai. The antioxidant, metal chelating and hydroxyl radical scavenging activity of dabai extract was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, Fe2+ chelating assay and the hydroxyl radical scavenging assay and found that it yielded an inhibition of 2.31%, 4.89% and 13.06% respectively. Then, chracterization using FTIR revealed the presence of flavonoids, anthocyanins and phenols serving as the potential bioactive compounds for the antioxidant activities. The knowledge gained from the antioxidant capacities and properties of dabai extract are potentially useful for the application of traditional plant medicine as an alternative nutraceutical product in the modern medical industry.